Drought tolerance of melon (Cucumis melo L.) genotypes using evapotranspiration and yield components in a semi-arid environment - Musa Seymen; Duran Yavuz; Ertan Sait Kurtar; Nurcan Yavuz; Önder Türkmen; Ünal Kal; Gülbanu Kıymacı; Banu Çiçek Arı (Agricultural Water Management, 2025)
Increasing drought all over the world, especially in semiarid regions, has made it difficult to access clean water resources for agriculture. In water-limited environments, farmers either use wastewater to irrigate their crops or apply severely restricted irrigation techniques with scarce clean water. In this study, 20 melon inbred line genotypes, 4 cultivars were evaluated for their seasonal evapotranspiration (ET) and yield components in a field test under full irrigation (I100) and 50 % water stress (I50) conditions for two years. Seasonal ET values calculated according to the soil-water budget method ranged from 373.3 to 594.3 mm in the 1st year and from 363.6 to 603.0 in the 2nd year. Seasonal ET underwent a significant decrease in the subjects receiving 50 % water stress, which led to serious losses of yield. Indeed, water stress, decreases in yield by 39 % and 42 %, on average, were recorded in 2023 and 2024, respectively. In addition, it negatively affected agro-morphological characteristics such as fruit number, fruit weight, fruit length, fruit width, and rind thickness. On the other hand, pH and soluble solid content in melon exposed to water stress significantly increased. Sürmeli F1 (G3) and Westeros F1 (G4) hybrid varieties showed a good performance in terms of yield components under both well-watered and water deficit conditions. Moreover, in the I100 treatment, the water crop productivity (WPc) of G3 and G4 was found to be higher than that of the standard cultivars and inbred line genotypes. Under I50 conditions, however, genotype G4 achieved the highest WPc, followed by G57, G62, G70, and G58. Results of the principal component analysis (PCA) indicated that genotypes G15, G40, G37, G62, and G79 and hybrid varieties G3 and G4, which occupied the same region on the PCA plot, were identified as water-stress tolerant genotypes based on yield components.